2017
DOI: 10.1175/jcli-d-16-0559.1
|View full text |Cite
|
Sign up to set email alerts
|

Observed Variability of Cloud Frequency and Cloud-Base Height within 3600 m above the Surface over the Contiguous United States

Abstract: The geographic and temporal variability of the surface–3600-m cloud frequency and cloud-base height over the contiguous United States for a 5-yr period (2008–12) and the interannual variations for a 16-yr period (2000–15) are described using information from the Automated Surface Observing System (ASOS) observations. Clouds were separated into four categories by the cloud amount reported by ASOS: few (FEW), scattered (SCT), broken (BKN), and overcast (OVC). The geographic distributions and seasonal and diurnal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 51 publications
2
22
0
Order By: Relevance
“…Other cloud and aerosol properties might also be important factors, for example, changes in cloud radiative properties, such as cloud optical thickness (Deneke et al, ; McCoy et al, ). Cloud height, which is relative to the distributions of low clouds, also impacts the variation in R s (An et al, ; Matuszko, ). Li et al () show that the variation in single‐scattering albedo has a substantial impact on the trend in R s .…”
Section: Discussionmentioning
confidence: 99%
“…Other cloud and aerosol properties might also be important factors, for example, changes in cloud radiative properties, such as cloud optical thickness (Deneke et al, ; McCoy et al, ). Cloud height, which is relative to the distributions of low clouds, also impacts the variation in R s (An et al, ; Matuszko, ). Li et al () show that the variation in single‐scattering albedo has a substantial impact on the trend in R s .…”
Section: Discussionmentioning
confidence: 99%
“…The colour bar indicates the scatter density, which is defined as the number of data dots in 100 × 100 axis grids. The solid lines are the best fit lines calculated using least squares regression and fog of the coast (see figure 5 of An et al, 2017). The weak correlation between monthly mean CBH simulated by NARR and observed by ASOS in the West Coast region is primarily caused by the decoupling of clouds and surface conditions.…”
Section: Evaluation Of Multi-year Averages Of Cbf and Cbh Against Omentioning
confidence: 98%
“…CBHs during precipitation are included because the ceilometer and micro-pulse lidar provide relatively accurate CBHs under large but sparse precipitation conditions (Clothiaux et al, 2000). When the intensity of precipitation is high enough that it obscures the CBH signal, the ASOS reports a vertical visibility (VV) calculated from the attenuation coefficient (Vaisala, 1989), and the proportion of VV cases is very low (less than 1%) over the CONUS (An et al, 2017). Besides, the precipitation identifications in the ASOS and NARR are different.…”
Section: Automated Surface Observing Systemmentioning
confidence: 99%
“…When the cloud base is completely obscured by precipitation or fog, the ceiling is reported as a vertical visibility (VV) instead of a cloud-base height. As in An et al (2017), cases in which the ceiling height is classified as ''VV'' are included in this study. Using these criteria, and compiling values across all stations, it was found that restrictive ceilings were observed more often in January (31%) than June (24%) 2019 with notably more MVFR ceiling heights occurring in January ( Table 2).…”
Section: Dataset Descriptionsmentioning
confidence: 99%